PELATIHAN KETERAMPILAN KEJURUAN GARMEN APPAREL DI LEMBAGA PEMASYARAKATAN NARKOTIKA KLAS II A KOTA LUBUKLINGGAU - Virry Grinitha; Agung Nugroho; Jamaludin Jamaludin; Cekman Cekman (LP4MK STKIP PGRI Lubuklinggau, 2023)
The purpose of community service between PGRI Silampari University, in collaboration with the Lubuklinggau City Manpower Service and the Lubuklinggau City Class II.A Narcotics Correctional Institution is to improve apparel garment vocational skills in the assisted community in Lubuklinggau Class II.A Narcotics Correctional Institution. Methods of community service activities include socialization, discussion, practice and evaluation of participants' responses to activities. Based on the results of community service activities, it is known: 1) There is collaboration between the PGRI Silampari Lubuklinggau university and the Lubuklinggau City Manpower Office and the Lubuklinggau City Narcotics Penitentiary. 2) Good and effective implementation of apparel garment vocational skills socialization activities. 3) Effective discussion activities increase the motivation of participants towards training activities. 4) The assisted community is able to practice the skills that have been provided by the resource persons, and 5) The activities are going well and effectively as seen from the results of the responses stating that the activities are very effective. Based on the results of the PKM activities that the team has carried out, it can be concluded that the PKM activities are going well and effectively in accordance with the needs of the assisted community of the Lubuklinggau City Narcotics Correctional Institution